Multi‐Dimensional Nano‐Additives for Their Superlubricity: Tribological Behaviors and Lubrication Mechanisms - Kang Yang; Yahui Xiong; Guijun Wu; Haibo Lin; Jun Tang; Chao Wu; Hongliang Chen; Yaqiong Wang (Advanced Materials Interfaces)
Abstract The significant contribution of super lubrication is to achieve ultra‐low friction in the friction pair, improving the wear resistance of the contact surface and thus achieving energy savings and environmental protection. Despite numerous experimental studies exploring the mechanism contributing to superlubrication, there is a relative scarcity of overall generalizations regarding the recent development of 0D–3D nanomaterials in superlubrication. Therefore, this paper systematically reviews the latest research progress on nanomaterials for achieving ultra‐low friction and wear in solid/liquid lubrication systems focusing on the structural characteristics of 0D‐3D nanomaterials. The important role of nanomaterial dispersion in the superlubrication steady state is discussed in detail, and recommendations are made for the key challenges of future engineering‐scale macroscopic superlubrication applications.